1975
DOI: 10.3758/bf03198201
|View full text |Cite
|
Sign up to set email alerts
|

A clarification of frequency effects in children’s discrimination learning

Abstract: Three experiments were conducted to assess the effects of certain stimulus variables on children's discrimination learning. In general, it was found that word frequency was negatively related to discrimination learning as long as the words were meaningful to Ss. Moreover, the relationship between word frequency and performance reversed in free-recall learning, as was expected. Equivalent relationships between frequency and learning were obtained with both verbal and pictorial materials. The implications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…There are a large number of studies which showed that verbal discrimination learning is easier when stimulus materials are pictorial rather than verbal Ghatala, Levin, & Makoid, 1975;Rowe, 1972;). Ghatala and Levin and their associates have attempted to discover why pictures are better stimulus materials than words in verbal discrimination learning tasks.…”
Section: Verbal Discrimination Learningmentioning
confidence: 97%
“…There are a large number of studies which showed that verbal discrimination learning is easier when stimulus materials are pictorial rather than verbal Ghatala, Levin, & Makoid, 1975;Rowe, 1972;). Ghatala and Levin and their associates have attempted to discover why pictures are better stimulus materials than words in verbal discrimination learning tasks.…”
Section: Verbal Discrimination Learningmentioning
confidence: 97%
“…Finally, the finding that meaningfulness seems to moderate the effect of background frequency in both frequency judgment and verbal discrimination tasks (Ghatala & Levin, 1974;Ghatala, Levin, & Makoid, 1975) suggests that the stability of situational frequency inputs to an item is positively related to the depth of processing of that item, in the Craik and Lockhart (1972) sense. Moreover, the present finding of an interaction between the frequency-meaningfulness pattern and pronunciation reinforces this view inasmuch as pronunciation may be thought of as inducing a deeper level of processing of Lo-F/Hi-M materials (though not of Lo-F/Lo-M materials) compared with when they are not pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, low-frequency words of low meaningfulness were judged no more accurately than high-frequency words (in fact, descriptively less accurately), a result not in accord with Weber's law, given the same assumption. 1 In a follow-up study, Ghatala, Levin, and Makoid (1975, Experiment 1) contrasted these same materials-high-frequency words (Hi-F), low-frequency/highmeaningfulness words (Lo-F/Hi-M), and low-frequency/low-meaningfulness words (Lo-F/Lo-M)-in a verbal discrimination task with sixth-grade children. The results corroborated the earlier interpretation inasmuch as [onlylthosey subjects in the Lo-F/Hi-M condition who could actually give semantic responses to the words (as determined from a subsequent definitions test) performed better on the discrimination task than comparable subjects in the Hi-F condition.…”
mentioning
confidence: 99%
“…It should perhaps be noted, however, that although the Weber's law postulate has received considerable support when item frequency is experimentally manipulated (situational frequency), the evidence suggesting an assimilation of background and situational frequency, and therefore, the operation of this postulate with respect to preexperirnental or background frequency, has been rather weak and limited as given in extensive reviews by Eckert and Kanak (1974) and Wallace (1972). Nevertheless, recent evidence by Ghatala, Levin, and Makoid (1975) provides support for the Weber's law prediction with preexperimental item frequency and thus makes reasonable an interpretation of the imagery effect in terms of the postulate. Ghatala and Levin (1976) demonstrated that when only objective frequency of concrete and abstract words is controlled, allowing abstract items to have higher phenomenal background frequency, the imagery effect in VDL is obtained.…”
mentioning
confidence: 82%